Introduction of the Utrecht Tasks for Attention in Toddlers Using Eye Tracking (UTATE): A Pilot Study - de Jong, Marjanneke; Verhoeven, Marjolein; Hooge, Ignace T. C.; van Baar, Anneloes L. (Frontiers in Psychology, 2016)
Attention capacities underlie everyday functioning from an early age onwards. Little is known about attentional processes at toddler age. A feasible assessment of attention capacities at toddler age is needed to allow further study of attention development. In this study, a test battery is piloted that consists of four tasks which intend to measure the attention systems orienting, alerting, and executive attention: the Utrecht Tasks of Attention in Toddlers using Eye tracking [UTATE]. The UTATE assesses looking behavior that may reflect visual attention capacities, by using eye-tracking methods. This UTATE was studied in 16 Dutch 18-month-old toddlers. Results showed that the instrument is feasible and generates good quality data. A first indication of sufficient reliability was found for most of the variables. It is concluded that the UTATE can be used in further studies. Further evaluation of the reliability and validity of the instrument in larger samples is worthwhile.